Firm/Employee Matching: An Industry Study of U.S. Lawyers. (March 2016) - Oyer, Paul; Schaefer, Scott
The authors study the sources of match-specific value at large U.S. law firms by analyzing how graduates of law schools group into law firms. They measure the degree to which lawyers from certain schools concentrate within certain firms and then analyze how this agglomeration can be explained by "natural advantage'' factors (such as geographic proximity) and by productive complementarities across graduates of a given school. Large law firms tend to hire from a select group of law schools, and individual offices within these firms are substantially more concentrated in terms of hires from particular schools. The degree of concentration is highly variable, as there is substantial variation in firms' hiring strategies. Two main drivers of variation in law school concentration occur within law offices. First, geography drives a large amount of concentration, as most firms hire largely from local schools. Second, school-based networks (and possibly productive complementarities) appear to be important because partners' law schools drive associates' law school composition even when controlling for firm, school, and firm/school match characteristics and when instrumenting for partners' law schools.